2008
DOI: 10.1111/j.1469-7580.2008.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical analyses of otoliths of the ice‐fish Chionodraco hamatus confirm a common origin with red‐blooded species

Abstract: The morphology and composition of the three otoliths of the Antarctic ice-fish Chionodraco hamatus were studied by scanning electron microscopy and X-ray diffraction. The composition of the sagitta, lapillus and asteriscus protein matrices was also analysed by sodium dodecyl sulphate-polyacrylamide gel electrophoresis, western blots and confocal laser scanning microscopy to reveal the presence of and to localize the calcium-binding proteins calmodulin, calbindin and S-100. Morphological results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…A comparison of lapillus and asteriscus otoliths indicates similarity in protein content ( Supplemental Table S2). Analogous results were previously reported for other fish species like Clupea harengus or Chionodraco hamatus (54,55). A report by Söllner et al (17) has shown that Stm is crucial for aragonite polymorph of zebrafish sagitta.…”
Section: Discussionsupporting
confidence: 86%
“…A comparison of lapillus and asteriscus otoliths indicates similarity in protein content ( Supplemental Table S2). Analogous results were previously reported for other fish species like Clupea harengus or Chionodraco hamatus (54,55). A report by Söllner et al (17) has shown that Stm is crucial for aragonite polymorph of zebrafish sagitta.…”
Section: Discussionsupporting
confidence: 86%
“…Lapillus of B-22 is matched to vaterite pattern instead of aragonite pattern, while most peaks of sagitta are matched to aragonite pattern and a few peaks are matched to vaterite pattern, as shown in Figure 5. Previous studies have shown CaCO 3 polymorphs differences in these three kinds of otoliths (Degens et al, 1969;Gauldie, 1993;Motta et al, 2009;Li and Feng, 2007). Most authors proposed that lapillus and sagitta are composed of aragonite, whereas asteriscus consists of vaterite (Motta et al, 2009;Li and Feng, 2007).…”
Section: Mineral Polymorphmentioning
confidence: 82%
“…Previous studies have shown CaCO 3 polymorphs differences in these three kinds of otoliths (Degens et al, 1969;Gauldie, 1993;Motta et al, 2009;Li and Feng, 2007). Most authors proposed that lapillus and sagitta are composed of aragonite, whereas asteriscus consists of vaterite (Motta et al, 2009;Li and Feng, 2007). However, the occurrence of vateritic lapillus and sigatta were also found in some fishes (Sweeting et al, 2004;Yang et al, 2007;Jessop, 2008), in which vateritic sagitta were found in cultured coho salmon and the authors supported that it was correlated with stress factors such as disease, poor water quality and temperature fluctuation (Sweeting et al, 2004).…”
Section: Mineral Polymorphmentioning
confidence: 82%
See 2 more Smart Citations